(untitled) (Semiárida, 2025)
This study evaluates the impact of Adaptive Management (MA) compared to Conventional Management (MC) on natural grasslands in Southwestern Buenos Aires, key ecosystems currently facing degradation risks due to overgrazing and woody plant encroachment. The research focused on measuring the Rangeland Health Index (RHI), a tool that synthesizes 15 field indicators to assess four fundamental ecosystem processes: the water cycle, mineral cycling, energy flow, and community dynamics. The trial was conducted at the Patagones Experimental Farm under a semi-arid climate. Two systems were compared: MC, characterized by continuous grazing with a fixed stocking rate (12 ha/AU), and MA, a management strategy based on biomimicry that utilizes high instantaneous stocking rates with planned rest periods to allow for vegetation recovery. At the beginning of the study in autumn 2021, no significant differences were recorded between the sites. However, after four years of implementation (2024), the MA treatment showed a substantial and statistically significant improvement in the RHI (p < 0.0001). Upon disaggregating the processes, MA had a positive impact on community dynamics, evidenced by greater vigor and presence of desirable perennial grasses and legumes, and on mineral cycling, through improved incorporation of litter and nutrients (manure/urine) into the soil. The energy flow and water cycle processes have not yet shown significant changes, suggesting that these indicators require longer periods to reflect improvements in arid environments. Adaptive Management is presented as an effective strategy to improve rangeland health and biodiversity, as by mimicking natural grazing patterns it enhances environmental sustainability and ecosystem resilience compared to continuous grazing.